2016
DOI: 10.7848/ksgpc.2016.34.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Autocorrelation of Disease Prevalence in South Korea Using 2012 Community Health Survey Data

Abstract: As a basic research to investigate geographical variations of diseases, this study analyzes and compares spatial patterns of 24 different diseases in South Korea using prevalence rate data provided by Community Health Survey in 2012. Descriptive statistical analysis, global Moran's I computation, and disease mapping were conducted to examine spatial associations and patterns of each disease. After the unique spatial patterns and distinctive spatial associations of each disease were observed, we concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Kim et al [ 7 ] confirmed that the prevalence of DM varied by region using stepwise regression analysis and decision trees. Other researchers also found that the prevalence of DM was significantly higher in rural areas and regions with a high proportion of the elderly population in Korea [ 8 ]. These results are similar to those of other studies abroad that analyzed the relationships of the degree of aging and socioeconomic level with DM at the regional level.…”
Section: Related Research Trends In Koreamentioning
confidence: 98%
“…Kim et al [ 7 ] confirmed that the prevalence of DM varied by region using stepwise regression analysis and decision trees. Other researchers also found that the prevalence of DM was significantly higher in rural areas and regions with a high proportion of the elderly population in Korea [ 8 ]. These results are similar to those of other studies abroad that analyzed the relationships of the degree of aging and socioeconomic level with DM at the regional level.…”
Section: Related Research Trends In Koreamentioning
confidence: 98%
“…The variables of individual-level and regional-level factors affecting hypertension prevalence in the regions (si/ gun/gu) were selected based on previous studies such as Lee [21], Kim and Kang [28], and Ewing [15].…”
Section: Selection Of Variablesmentioning
confidence: 99%
“…As described above, it has been found that the prevalence rate of chronic diseases is different according to the spatial specificity of the region, and there are differences depending on the regional variables [20,28]. For these reasons, there is a need for research to identify regional-level factors related to hypertension prevalence through spatial analysis that reflects the spatial dependence, which is a unique geographical feature of space.…”
Section: Spatial Distribution Of Hypertension Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Although levels of air pollutants including SO 2 , NO 2 , and PM 10 in major cities have not considerably increased in the last 10 years [ 31 ], air pollution in Seoul, particularly PM 10 , has increased more compared to other large cities such as Paris, Los Angeles, and London [ 32 , 33 ]. A small number of studies on allergic diseases conducted in Korea have taken into account spatial autocorrelation in ambient air pollutants [ 34 , 35 ], while others focus upon the prevalence of allergic diseases [ 36 ]. However, no studies simultaneously account for spatial autocorrelation in their bivariate analysis.…”
Section: Introductionmentioning
confidence: 99%